When space remembers: Death rises in the East (REVISTA NODO, 2026)
This research analyzes the artistic project La muerte sale por Oriente (2014-present) developed by the artist Sonia Madrigal. It consists of a documentary photography record, an artistic action, and the construction of a collective map. The research examines how the project carries out a public intervention to confront and denounce gender-based violence in highly marginalized spaces. Accordingly, the aim of this text is to explain that La muerte sale por oriente functions as a tool of denunciation and struggle against gender- based violence, as it operates through an aesthetic–affective experience intended to transform the symbolic structures that constitute gender-based violence. At the same time, the text is grounded in the theoretical frameworks of Patricia Hill Collins, Andrea Giunta, Mara Polgovsky, and Rosalyn Deutsche. It also incorporates a methodology drawn from feminist studies and art theory.
Keywords: Public Art; Femicide